Electrode microstructure controls localized electronic impedance in Li-ion batteries. (20th February 2019) - Vogel, John E.; Forouzan, Mehdi M.; Hardy, Emilee E.; Crawford, Sean T.; Wheeler, Dean R.; Mazzeo, Brian A.
Abstract: Substantial heterogeneity and defects in lithium-ion battery films can be a cause of material and battery failure. Although non-uniformity has been observed previously, the physical origin of electronic impedance non-uniformities in cathode materials has not been well-studied. We show that the local microscopic structure of materials strongly affects the resulting local impedance as measured by a micro-four-line probe, demonstrates large variation, and that these variations occur over sub-millimeter and larger distances on two different commercial cathode materials. These experimental results are further compared to modeled electronic and ionic transport pathways through the observed structure. By elucidating the extent and origins of heterogeneity in battery electrode films we provide a key principle through which batteries can be optimally designed to increase their safety, energy density, power, and longevity.